Cheminements écoliers dans un shared space : l’urbain au service des apprentissages - Melissa Bellesi; Maribel Casas (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
« Learning » the city is a universal and formative lesson, especially for young children. In this sense, the journey between home and school often constitutes the very first exploration of a regulated and shared social space. This paper proposes to examine the determinism that may exist between the urban configuration of the school space and the preferred modes of travel to access it : could a specific spatial arrangement around schools alleviate the congestion generated by minute drop-offs and contribute to a resurgence in the use of walking — or ‘soft’mobility — in order to make the journey between home and school a learning-rich space-time ? Would rethinking the space surrounding schools help to reinstate a spatial dynamic and a sense of place and citizenship ?